Economic growth and emissions: Testing the Environmental Kuznets Curve hypothesis for ECOWAS countries - Douglason Godwin Omotor (West African Journal of Monetary and Economic Integration, 2017)
The objective of this paper is to establish whether the estimated relationship between environmental degradation and per capita income corroborates the inverted U-shape hypothesis as exemplified by the Environmental Kuznets curves (EKCs) in selected ECOWAS countries. Considering two variants of emissions-sulfur dioxide (SO2) and carbon dioxide (CO2) and using panel fixed and random effects estimation techniques, the study indicates the existence of EKCs for the two variants of environmental quality. Experimentation with augmented quadratic equations, however, does not in some cases produce consistent results for SO2; while cubic polynomial forms suggest N-shaped EKCs for CO2.The turning points estimated for the two indicators of environmental quality are relatively low, which suggests a demonstration of the low level of development in the sub-region that may be related to high incidence of poverty. The major drivers of SO2 in the sub- region are fuel processing and fuel combustion led by Nigeria. For CO2 emissions, it is driven by rapid population growth that is equally induced by Nigeria. The polity variable which interacted significantly with the income variable to create the inverted-U shape EKC signals the importance of public institutions in the enhancement of environmental quality. Although ECOWAS countries may have benefited from early learning effects and environmental awareness, the implication is that policymakers must be proactive to sustain the current trend as the region enters the phase of industrialization and may not necessarily wait for a long time to improve environmental conditions as is the case with developed countries. This can be accomplished by using environmental tax instruments such as fuel tax which has been advised to be progressive for some African countries. By way of recommendation, a functional population policy should be implemented particularly in Nigeria.
Keywords: I15; O13; O44; Q50; Q53; 330; Environmental Kuznets Curve; ECOWAS; Economic growth; Emissions; Sulfur dioxide; Carbon dioxide